Normal values for maximal respiratory pressures in children and adolescents: A systematic review with meta-analysis - Pradi, Nicole (2024)
Background: The non-invasive assessment of maximal respiratory pressures (MRP) reflects the strength of the respiratory muscles. Objective: To evaluate the studies which have established normative values for MRP in healthy children and adolescents and to synthesize these values through a meta-analysis. Methods: The searches were conducted until October 2023 in the following databases: ScienceDirect, MEDLINE, CINAHL, SciELO, and Web of Science. Articles that determined normative values and/or reference equations for maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) in children and adolescents published in English, Portuguese, or Spanish regardless of the year of publication were included. Two reviewers selected titles and abstracts, in case of conflict, a third reviewer was consulted. Articles that presented sufficient data were included to conduct the meta-analysis. Results: Initially, 252 studies were identified, 28 studies were included in the systematic review and 19 in the meta-analysis. The sample consisted of 5798 individuals, and the MIP and MEP values were stratified by sex and age groups of 4–11 and 12–19 years. Values from females 4–11 years were: 65.8 cmH2O for MIP and 72.8 cmH2O for MEP, and for males, 75.4 cmH2O for MIP and 84.0 cmH2O for MEP. In the 12–19 age group, values for females were 82.1 cmH2O for MIP and 90.0 cmH2O for MEP, and for males, they were 95.0 cmH2O for MIP and 105.7 cmH2O for MEP. Conclusions: This meta-analysis suggests normative values for MIP and MEP in children and adolescents based on 19 studies.